SEPARATE THEORETICAL BASIS OF INTERNAL ORGANIZATIONAL ACTIVITIES OF PUBLIC GOVERNMENT BODIES (Bulletin of criminological association of Ukraine, 2023)
The article examines the legal essence of the mechanism of administrative and legal regulation in the context of the activities of public authorities. It has been established that the fundamental element of this process is administrative and legal relations that arise in connection with the activities of one or another public authority, including state law enforcement agencies.It is emphasized that it is administrative-legal relations that determine the dynamic directions of administrative-legal regulation, given that legal relations directly sublimate the rules of behavior declared by law into the actual actions of legal entities. Common and distinctive features of public administration and intra-organizational activities of state authorities as the main directions of their functioning are analyzed.It is noted that the specified processes should not be equated, since intra-organizational activity is a separate element of the subject of administrative and legal regulation, regulated by relevant norms and in its essence constitutes a type of administrative and legal relations.
Keywords: public administration; state authorities; mechanism of administrative and legal regulation; intra-organizational activity.